Pengembangan Potensi Atraksi Wisata Gastronomi di Desa Cililin Kabupaten Bandung Barat - Ayunda Fitrah Tunisya; Dela Safitri; Asep Parantika (Jurnal Ilmiah Wahana Pendidikan, 2023)
Cililin Village, Cililin District, West Bandung Regency offers many opportunities for research and development as a tourist destination. One of them is the famous Cililin Wajit. Wajit Cililin has been produced and sold in its product form for a long time. However, there is one interesting aspect that has not been well developed, namely the production process. The purpose of this research is to demonstrate the potential of Cililin properties for tourism development. The research method used is qualitative method. Primary data collection is done through observation and in-depth interviews. In addition, a literature search was carried out. Data analysis uses an interactive model with three simultaneous functions: data reduction, data representation and reasoning. The results of the study show that the process of making cili wajit can become a gastronomic tourism object and an educational tour because of its interesting uniqueness. This attraction can only be shown to tourists by local residents who have experience in processing and manufacturing it, so that the local community must be involved in its development